110k views
2 votes
Which equation gives the rule for this tablex: 3, 4, 5, 6y: -3, -4, -5, -6A: y = -x - 3B: y = -x + 1C: y = -x - 9D: y = -x

User Pawels
by
4.9k points

1 Answer

5 votes

The slope-intercept form of a line is:

y = mx + b

where m is the slope and b is the y-intercept

The slope of the line that passes through the points (x1, y1) and (x2, y2) is computed as follows:


m=(y_2-y_1)/(x_2-x_1)

Replacing with the points (3, -3) and (4, -4), we get:


m=(-4-(-3))/(4-3)=-1

Replacing with point (3, -3) and m = -1 into the equation,

-3 = (-1)(3) + b

-3 = -3 + b

-3 + 3 = b

0 = b

Then, the equation is:

y = -x

User Steven Combs
by
5.7k points